Dialogue Translation Quality Analysis in Indonesian Version of The Little Prince - Excelsaputri, Ellysabeth Sahasrara; Darta, Deta Maria Sri (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2025)
Dialogue relates to the character’s feelings and attitude, so delivering them the same way as the SL is important and it can be crucial. In translating dialogues, a shift may occur from SL to TL. Shifts that occur may affect the quality of the dialogue translation. It can lead to a misrepresentation of the character’s feelings and attitudes. Therefore, this paper examines the shifts and the quality of translation. This research uses qualitative descriptive to categorize the shifts using Catford’s (1965) category shift and analyze its quality with Nababan’s (2021) accuracy assessment. There are  95 data found in total, where 87 data were considered accurate, 6 data were considered less accurate, and 2 data were considered inaccurate. The result shows a total range scale of 2,8 accurate points. It indicates when the shifts are applied correctly, they can deliver the feelings and attitudes of the characters naturally in the TL.